Eastern Dimension of the European Neighbourhood Policy: Europeanization Mutual Trap - V. A. Latkina (Vestnik MGIMO-Universiteta)
The article analyses the Europeanization policy of the European Union towards the Eastern Partnership participant countries. Suffering from the lack of clear strategy and ultimate goal in the European Neighbourhood Policy the European Union enhances external democratization and its governance in post soviet states without immediate Union's membership perspective. Underestimation of common neighbourhood geopolitical duality in the context of growing rivalry between European (EU) and Eurasian (Custom Union/Eurasian Economic Union) integration gravitation centers presents the Eastern partners of the EU with a fierce dilemma of externally forced immediate geopolitical and civilizational choice while not all of them are well prepared to such a choice. The mutual Europeanization trap here to be studied both for the EU and its Eastern partners (involving Russia) is a deficiency of regulating cooperation mechanism in the situation of European and Eurasian free trades zones overlapping. Vilnius Summit 2013 results test the "European aspirations" of the New Independent States and upset the ongoing process of the European Neighbourhood Policy in the context of growing economic interdependence in Wider Europe. Besides, the Ukrainian crisis escalation during 2014 as a new seat of tension provokes unbalance of the whole European security system and creates new dividing lines in Europe from Vancouver to Vladivostok.